Characterization of the Performance of the Enerflow Cyclone Burn Grate (ECBG) for the Treatment of Hazardous Waste at an Isolated Diesel Power Plant - Yunita Fahmi; Rizkianti Marselina; Matthew Savio Kurniawan (Eduvest - Journal of Universal Studies, 2026)
As the world’s largest archipelagic nation, Indonesia faces significant challenges in managing hazardous and toxic waste (B3) generated by diesel power plants (PLTD) in isolated areas. The Portable Turbo Burn Incinerator RC80 manufactured by Scholer Industries Australia, which was modified by PT Enerflow Engineering Indonesia into the Enerflow Cyclone Burn Grate (ECBG), also known as the Mini Turbo Incinerator (MTI), incorporates several technical modifications, including a 14-meter chimney, wet scrubber integration, a two-stage combustion chamber, and industrial design rights protection to comply with Indonesian regulatory requirements. This study aims to comprehensively characterize the combustion efficiency and operational performance of ECBG at various feed rates using liquid and solid B3 waste through field testing at the Pongok Island PLTD. Field tests were conducted under three experimental scenarios with varying total waste masses (36.5 kg, 40.0 kg, and 44.0 kg) and combustion durations ranging from 1.0 to 2.0 hours. The evaluated performance parameters included combustion temperature, burn rate, waste destruction efficiency, and emission characteristics. The results demonstrate that ECBG achieved an average waste destruction efficiency of 95.2%, with a maximum volume reduction of 98% under optimal operating conditions. The combustion rate ranged from 18.25 to 44.00 kg/hour, depending on waste composition and operational parameters. The integrated wet scrubber system effectively controlled exhaust gas emissions and complied with BAPEDAL quality standards. This research provides the first comprehensive performance characterization of a locally modified thermal treatment technology with wet scrubber integration and intellectual property protection for B3 waste processing in isolated power plant environments.